Analisis Pengaruh Ulasan Produk, Persepsi Harga, Dan Live Streaming Marketing Terhadap Minat Beli Produk Halal Di Tiktok Shop - Hany Meridha Isnaeni; Evan Stiawan; Debby Arisandi (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to explore the impact of product reviews, price perceptions, and live-streaming marketing on purchase intent for halal products on TikTok Shop. The rapid growth of social commerce, particularly through TikTok Shop, has transformed the way consumers shop online. The methodology used in this study is a quantitative approach involving 397 Generation Z respondents in Bengkulu City. Data collection was conducted by distributing a Likert-scale questionnaire. Data analysis was performed using SPSS, including validity and reliability testing, classical assumption tests, multiple linear regression analysis, t- and F-tests, and the coefficient of determination (R²). The research findings indicate that product reviews, price perception, and marketing via live streaming have a positive and significant influence on purchase intent, both individually and collectively. Among these variables, marketing via live streaming was found to have the most dominant impact. The coefficient of determination indicates that 53,8% of the variation in purchase intent can be explained by these three variables.